2019
DOI: 10.1038/s41598-019-44891-z
|View full text |Cite
|
Sign up to set email alerts
|

3D-printed sound absorbing metafluid inspired by cereal straws

Abstract: Used as building biomaterials for centuries, cereal straws are known for their remarkable acoustic performances in sound absorption. Yet, their use as fibrous media disregards their internal structure made of nodes partitioning stems. Here, we show that such nodes can impart negative acoustic bulk modulus to straw balls when straws are cut on either side of a node. Such metafluid inspired by cereal straws combines visco-thermal diffusion with strong wave dispersion arising from quarter-wavelength resonances wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…While photonic structures have been proven to exist in several natural systems 7 , 8 , most of the sustainable acoustic or elastic metamaterials are either man modified 9 or bio-inspired 10 , 11 . Very recently 12 , the first natural ultrasonic metamaterial was reported.…”
Section: Introductionmentioning
confidence: 99%
“…While photonic structures have been proven to exist in several natural systems 7 , 8 , most of the sustainable acoustic or elastic metamaterials are either man modified 9 or bio-inspired 10 , 11 . Very recently 12 , the first natural ultrasonic metamaterial was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Trabelsi and Kammoun [64] noted that treated straw bale with cement has a similar sound absorption coefficient compared to untreated straw bale and concluded that effect of straw treatment has minimal effect on the sound properties. There is also research from Huang et al [65] on creating acoustic bio-metamaterials based on straw characteristics, and in the same study provided a comprehensive explanation of the acoustic properties of straw based on the design of strawinspired metafluid (MCS).…”
Section: Sound Absorption Coefficient Amentioning
confidence: 96%
“…This induced roughness was found to strongly affect the thermal and viscous losses when of dimension comparable to the spacing between adjacent surfaces 33 . A close-up image of the SRR neck is shown in Fig.…”
Section: (B-e)mentioning
confidence: 97%
“…Three others are direction-dependent [τ ∞ jj ; Λ j ; K 0 jj ] and related to viscous effects, respectively the high-frequency limit of tortuosity, the characteristic viscous length and the viscostatic permeability in the direction e j . Although the transport parameters can be estimated by FEM problems at the scale of the unit cell 36,37 , it has been shown that manufacturing defects play an important role in the measured effective properties 31,33 . In order to account for the internal geometrical defects, we rely on databases obtained from inverse characterisation techniques 4,38 .…”
Section: A Equivalent Fluid Modelmentioning
confidence: 99%